Development of a new clinical decision rule for cervical CT to detect cervical spine injury in patients with head or neck trauma. Issue 10 (21st July 2018) - Inagaki, Takeshi; Kimura, Akio; Makishi, Go; Tanaka, Shigeru; Tanaka, Noriko
Abstract : Objective: Previous cervical spine imaging decision rules have been based on positive findings on plain X-ray and are limited by lack of specificity, age restrictions and complicated algorithms. We previously derived and validated a clinical decision rule (Rule 1) for detecting cervical spine injury (CSI) on CT in a single-centre study. This recommended CT for patients with (1) GCS score <14, (2) GCS 14–15 and posterior cervical tenderness or neurological deficit, (3) age ≥60 years and fall down stairs, or (4) age <60 and injured in a motorcycle collision or fallen from height. This study assessed the accuracy and reliability of this rule and refined the rule. Methods: We conducted a prospective, dual-centre study at two Japanese EDs between August 2012 and March 2014. Patients with head or neck injury ≥16 years of age were included. Clinical data were collected from medical records. Imaging was at the discretion of the treating physician. CSI was diagnosed as a fracture or dislocation seen on CT; patients who were not imaged were followed for 14 days. We analysed the sensitivity and specificity of Rule 1 and refined it post hoc using recursive partitioning. Results: 1192 patients were enrolled. 927 completed follow-up. Of these, 584 (63.0%) underwent CT imaging and 38 had CSI. Sensitivity and specificity of Rule 1 were 92.1% (95% CI 79.2% to 97.3%) and 58.6% (95% CI 55.4% to 61.9%). A second rule (Rule 2) was derived recommending CT for those with any of the following: GCS <14, cervical tenderness, neurological deficit or mechanism of injury (fall down stairs, motorcycle collision or fall from height) without age limits. Sensitivity and specificity were 100% (95% CI 90.8% to 100%) and 51.9% (95% CI 48.6% to 55.2%), respectively. Conclusions: Our initial CT decision rule had lower sensitivity than in our initial validation study. A refined decision rule based on GCS, neck tenderness, neurological deficit and mechanism of injury showed excellent sensitivity with a small loss of specificity. Rule 2 will now need validation in an independent cohort.